Metabolic and hormonal responses to acute high-load resistance exercise in normobaric hypoxia using a saturation clamp - Jiang, Guole; Qin, Shuang; Yan, Bing; Girard, Olivier (Frontiers in Physiology, 2024)
Introduction We assessed metabolic and hormonal responses to high-load resistance exercise under varying normobaric hypoxia conditions with a saturation clamp. Methods Employing a counterbalanced, crossover test design, ten well-trained men participated in three exercise trials with normoxic or hypoxic gas mixtures to maintain arterial oxygen saturation at −90% and 80% [moderate (MH) and severe (SH) hypoxia, respectively]. The resistance exercise regimen comprised five sets of 10 repetitions of barbell back squats at 70% of one repetition maximum, with 1-min rest between sets. Metabolic and hormonal responses were measured before normoxia or hypoxia exposures (Pre 1), 15 min after the exposures (Pre 2), and at 0-, 15-, and 30-min post-exercises (T0, T15, and T30, respectively). Results Compared to Pre 2, blood lactate concentrations and growth hormone values were elevated at T0, T15, and T30 (p ≤ 0.001), while testosterone values increased at T0 in all conditions (p ≤ 0.009). Epinephrine values increased significantly from Pre 2 to T0 in SH only (p < 0.001). SH had significantly higher blood lactate concentrations (p = 0.023), growth hormone (p = 0.050), and epinephrine (p = 0.020) values at T30 compared to NM. Cortisol values were elevated above Pre 2 at T15 in MH and SH, while lower testosterone values were noted at T0 and T15 for SH compared to NM and MH (all p ≤ 0.05). Discussion Severe simulated hypoxia, achieved through a saturation clamp during barbell back squats, may enhance metabolic and hormonal responses, particularly 30 min post-session. Nevertheless, the acute effects of hypoxia exposure seem to be overridden by the impact of high-load resistance exercise.